THE DEVELOPMENT OF A 5W + 1H BASED POCKET BOOK ON THE KINGDOMS HISTORY MATERIAL TO IMPROVE READING LITERACY OF GRADE 4 ELEMENTARY STUDENTS - Laila Fatmawati; Subkhi Fajrikah (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract. This research was motivated by the problems found in elementary schools, which are students’ low literacy ability and lack of supporting books in learning. This research aimed to develop pocket book teaching material, determine the feasibility and the effectiveness of the 5W + 1H based pocket book on the kingdoms history material to improve reading literacy in the fourth grade elementary school students. The Development Procedure used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Small group trial subjects were 10 students from grade IV Shidiq and large group trials were 28 students from grade IV Amanah. While the operational field trial were conducted on 30 students from grade IV Fatonah and Tabligh. The results of the research on the feasibility test of media expert got a score of 78,91 with the category of "very feasible", material expert got a score of 93,2 with the category of "very feasible", learning expert got a score of 93,2 with the category of "very feasible", and language expert got a score of 85,4 with the category of "very feasible". In the assessment of the response of the teachers got a score of 93,62 with the category "very feasible" and the assessment of grade 4 students got a score of 97,82 with the category of "very feasible". The effectiveness was tested using One-Group Pretest-Posttest Design and analysis using the normality test and Paired T-test. In the normality test, the data obtained were normally distributed with a significance value of pretest 0,98 and posttest (200). While in the Paired T-test, the average score is 69,00 pretest and posttest and the results of the significance (p) is 0,000 and smaller than the significance of 0.05 (0,000 <0.05).